(3eZfi GdeMJGL Edi eYQaI CdaGX GdefgGLs - (3CHh YHO Gdgd eMeO GdNWjH GdTQHjfis; (3Gdfhhj,J (B676 (3g` s ((3CMeO GdOefghQi s)
(3ChdgG (B:s
(3GdMeO ddg GdZfi GdeZfi GdcQje GdaJGM hHYO deG jSQ Gddg GdaQGZ ef TQMi Ydi GdJfHjg MeOi Gddg Ydi EJeGeg Ke SCdfi HYV CUMGHi Cf CLYd eKdg Ydi efgGL GdfhGhi , aJQOOJ s
(3BNQgG (B:s
(3hJSf GdfbjYI , hgj WYGe jYed dbOhe GdeSGaQ , hSjCJi ai GdhdjeI HjGfgG hbO Je TQM GdQHY GdChd HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJH eJf GdefgGL HGdMeQIs
(3Ydi GdfSNI JedcGJ ai GdbQf GdKGdK YTQ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdabg GdTGaYjs